Strategi BAZNAS Kabupaten Bogor dalam Mengelola Zakat Produktif untuk Pemberdayaan UMKM Mustahik - Haudaa Rizki, Muhamad Dhiya; Hakim, Nurman; Muhlisin, Sofian (Lembaga Yasin AlSys, 2025)
The management of productive zakat is a strategic instrument for improving the welfare of mustahik through empowerment-based strengthening of microenterprises; however, the effectiveness of its implementation depends heavily on the strategies adopted by zakat management institutions in designing program planning, implementation, and supervision. This study aims to conduct an in-depth analysis of the strategies of BAZNAS Bogor Regency in managing productive zakat and to examine the extent to which these programs are able to empower mustahik MSMEs. Using a qualitative approach with a case study design, data were collected through in-depth interviews, field observations, and program document analysis, and were then analyzed interpretively. The findings show that the productive zakat management strategy of BAZNAS Bogor Regency is implemented through needs-based planning grounded in the actual conditions of mustahik, organizational arrangements that involve local partnerships, the disbursement of business capital accompanied by mentoring, and continuous supervision through periodic monitoring. The results further indicate that the success of MSME empowerment is strongly influenced by the quality of the initial needs analysis, the relevance of the financing schemes, and the consistency of the mentoring received by mustahik. The study concludes that productive zakat has strong potential to enhance economic self-reliance if managed through an integrated strategic approach, and recommends strengthening long-term monitoring–evaluation practices and expanding comparative inter-regional studies to enrich zakat-based empowerment models.